How to be a pirate - Cowell, Cressida (How to train your dragon ;, 2005)
Follows the further adventures and misadventures of Hiccup Horrendous Haddock the Third as his Viking training continues and his father leads a stranger and the Hairy Hooligans to the Isle of Skullions in search of a pirate's treasure.